Aproximaciones al problema de los tres cuerpos (un caso particular de la dinámica estelar) - Altavista, Carlos Alberto (1980)
The object of this paper is to give a brief account of the results obtained by Poincaré in his studies of the convergence of series which satisfy formally the differential equations of motion and to look for the possibility that the application to a particular case of dynamics be successful. It is well known that Poincaré has deal with equations of the form.